Abundance of Procamallanus (Spirocamallanus) inopinatus (Nematoda: Camallanidae) in Characiformes fish and associated factors in Midwest Brazil - RAFAEL B. AMARAL; GABRIELLY R. LEÃO; THIAGO N.S. CAMPOS; KARINE M. BORGES; MAYRA I. GRANO-MALDONADO; CIRO N.R. LINO; RICARDO M. TAKEMOTO; THIAGO L. ROCHA; LUCIANA DAMACENA-SILVA (Anais da Academia Brasileira de Ciências, 2023)
Abstract The success of Procamallanus (Spirocamallanus) inopinatus infection in fish involves a complexity of variables. This study aims to evaluate the relationship between abundance of P. (S.) inopinatus with biometric and somatic parameters, sex, relative condition factor (Kn) and hosts diet, as well as to evaluate length relationship of the parasites and the hosts. The fishes were collected by the mesh method and data, length, weight, sex, gonad and liver weight, Gonadosomatic index (GSI) and hepatosomatic index (HSI), Kn and stomach content were recorded. Twenty-seven specimens of P. (S.) inopinatus were collected in the intestine from Serrasalmus rhombeus and 52 from Leporinus friderici. In general, the prevalence, mean intensity and mean abundance of infection was higher in L. friderici. The total abundance was explained by the variables GSI, HSI total length, gonad and liver weight. Fish relative condition factor (kn) and sex were not influenced by the infection, being that the parasite infection did not impair the body condition of the hosts. There is no relationship between host length and parasite length in any of the evaluated fish species. On average, S. rhombeus parasites are 0.69 cm larger than L. friderici parasites.